Altered functional brain connectivity in Dyt1 knock-in mouse models - R. Z. Adury; B. J. Wilkes; P. Girdhar; Y. Li; D. E. Vaillancourt; D. E. Vaillancourt; D. E. Vaillancourt (Dystonia)
DYT1 dystonia is an early onset, generalized form of isolated dystonia characterized by sustained involuntary muscle co-contraction, leading to abnormal movements and postures. It is the most common hereditary form of primary dystonia, caused by a trinucleotide GAG deletion in the DYT1 gene, which encodes the TorsinA protein. Recent studies conceptualized dystonia as a functional network disorder involving basal ganglia, thalamus, cortex and cerebellum. However, how TorsinA dysfunction in specific cell types affects network connectivity and dystonia-related pathophysiology remains unclear. In this study, we aimed to elucidate the impact of the GAG TorsinA mutation present globally and when restricted to the cortical and hippocampal neurons. To accomplish this, we generated two distinct Dyt1 mouse models, one with Dyt1 dGAG knock-in throughout the body (dGAG) and another with a cerebral cortex-specific Dyt1 dGAG knock-in using Emx1 promoter (EMX). In both models, we performed in vivo neuroimaging at ultra-high field (11.1T). We employed functional magnetic resonance imaging (fMRI) to assess resting-state and sensory-evoked brain connectivity and activation, along with diffusion MRI (dMRI) to evaluate microstructural changes. We hypothesized that dGAG mice would exhibit widespread network disruptions compared to the cortex-specific EMX mice, due to broader TorsinA dysfunction across the basal ganglia and cerebellum. We also hypothesized that EMX mice would exhibit altered functional connectivity and activation patterns, supporting the idea that TorsinA dysfunction in the sensorimotor cortex alone can induce network abnormalities. In dGAG animals, we observed significantly lower functional connectivity between key sensorimotor nodes, such as the globus pallidus, somatosensory cortex, thalamus, and cerebellum. EMX mice, while showing less extensive network disruptions, exhibited increased functional connectivity between cerebellum and seeds in the striatum and brainstem. These functional connectivity alterations between nodes in the basal ganglia and the cerebellum in both dGAG, EMX models underscore the involvement of cerebellum in dystonia. No significant structural changes were observed in either model. Overall, these results strengthen the concept of dystonia as a network disorder where multiple nodes across the brain network contribute to pathophysiology, supporting the idea that therapeutic strategies in dystonia may benefit from consideration of network properties across multiple brain regions.